Language skills needed by nurses aiming to work abroad: A need analysis of English for Nursing - Muntasir, Muntasir; Nurviani, Rahima (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2020)
This qualitative study explored the essential English language skills that should be prepared by nurses to be eligible to work and adapt in English native speaking countries. The study also provided the information on what kind of topics or materials that should be taught to prepare the nurses who might take the English proficiency test as one of the requirement to work aboard. This study used literature review and interview as the techniques to collect the data. The literature review summarized various sources while the interview obtained data from the nurses as the respondents of this study. The results of this study showed that the nurses who wanted to work aboard need to prepare and excel their communication skill in English in order to ease them in activities such as small talk, oral and written reports, etc. Besides, mastering medical terms is also important for the nurses as it relates to their professional work.